Thermoplastic composite from flaker waste / Nik Norhafizah Daud - Daud, Nik Norhafizah (2003)
In this study, particleboard flaker waste was used to produce thermoplastic composite. Tests such as bending, tensile, thickness swelling and water absorbtion were carried out. Filler loading of 10%, 30% and 50% was used. The result showed that 10% of flaker waste is most the suitable giving high strength compared to the 30% and 50% filler loading. MAPP used as a coupling agent increases the strength of the thermoplastic. For thickness swelling and water absorption values composites with 10% filler loading showed better stability. Flaker waste was found to be suitable filler in the manufacture of thermoplastic composite using polypropylene as the matrix.